Femmes des anti-Lumières, femmes apologistes - Albertan-Coppola, Sylviane (Études sur le XVIIIe siècle, 2016)
This book questions the place occupied by women, reputed to be "quarrelsome" according to Richelet, in the polemical exchanges supposed to guarantee their faith and put a mute to the words of "philosophy" of the Enlightenment.